SIFAT FISIS BAMBU SEPANJANG BATANG PADA BAMBU SERO (Schizostachyum brachycladum Kurz.) - Luanmasse, Alfi Dandi; Liliefna, Leonard Dantje; Fransz, J. J. (MAKILA, 2023)
The objective of this study was to analyze the effect of internode position along the culm on the physical properties of sero bamboo. This study used a randomized complete block design with internode position along the culm as the treatment effect, comprising six levels, i.e., 0, 20, 40, 60, 80, and 100%, using four bamboo culms as blocks. The observed response variables were the bamboo's physical properties, such as green and air-dry moisture content, radial, tangential, longitudinal shrinkage, and specific gravity. The result of the study showed that green moisture content radial and tangential shrinkage, statistically, were influenced by their locations along the culm. In contrast, air-dry moisture content, longitudinal shrinkage, and specific gravity were independent of their locations along the culm.